2014
DOI: 10.1149/2.011405jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multi-Walled Carbon Nanotubes Incorporation on the Structure, Optical and Electrochemical Properties of Diamond-Like Carbon Thin Films

Abstract: We report the effect of incorporation of multi-walled carbon nanotubes (MWCNT) on the mechanical, structural, optical and electrochemical properties of diamond-like carbon (DLC) thin films. The DLC/MWCNT hybrid composite was deposited onto stainless steel and quartz substrates by plasma enhanced chemical vapor deposition at low temperature (∼100 • C). Raman spectra of DLC/MWCNT film have characteristics from both DLC and MWCNT. The optical bandgap energy decreases with the incorporation of nanotubes. Scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
0
16
0
3
Order By: Relevance
“…Uma linha adicional de hidrogênio (1) passa através de um borbulhador contendo óxido de boro dissolvido em metanol numa concentração de 30000 ppm B/C, o qual é arrastado numa concentração que depende da temperatura, pressão de hidrogênio no borbulhador e fluxo de hidrogênio (22) . 3 B é produzido, sendo a substância contendo boro adicionada à fase gasosa de crescimento. Foi utilizado um rotâmetro para o controle do fluxo da mistura gasosa que saia do borbulhador para o interior do reator.…”
Section: Parte Experimental Crescimento Dos Filmes Ddbunclassified
See 2 more Smart Citations
“…Uma linha adicional de hidrogênio (1) passa através de um borbulhador contendo óxido de boro dissolvido em metanol numa concentração de 30000 ppm B/C, o qual é arrastado numa concentração que depende da temperatura, pressão de hidrogênio no borbulhador e fluxo de hidrogênio (22) . 3 B é produzido, sendo a substância contendo boro adicionada à fase gasosa de crescimento. Foi utilizado um rotâmetro para o controle do fluxo da mistura gasosa que saia do borbulhador para o interior do reator.…”
Section: Parte Experimental Crescimento Dos Filmes Ddbunclassified
“…A análise por Espectroscopia Raman constatou a boa dopagem destes filmes com o elemento boro. Uma importante característica observada foi a boa aderência dos filmes no substrato de titânio com a predominância nestes de carbono do tipo sp 3 .…”
Section: Conclusõesunclassified
See 1 more Smart Citation
“…Carbon is a very attractive material for electrochemical applications due to its different allotropes (fullerenes, nanotubes, graphene and diamond) of dimensionality from 0D to 3D [1,2]. Carbon materials can be prepared in various microtextures from powders to freestanding fibres, foams, amorphous, crystals and composites [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The DLC corrosion resistance is significantly dependent on the film composition and structure, which are strongly related to deposition technique, precursor gas and incorporated metals [8,9]. The incorporation of metals into the DLC matrix has shown to be effective for the reduction of film stress, improved hardness, toughness and corrosion resistance by increasing sp 3 content [10][11][12][13][14][15][16][17]. Morrison et al showed the incorporation of silver and platinum nanoparticles into diamond-like carbon matrix prepared using a multicomponent target pulsed laser deposition process [10].…”
Section: Introductionmentioning
confidence: 99%